2021
DOI: 10.12669/pjms.38.icon-2022.5789
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and outcomes of patients with different resistance patterns of Salmonella enterica

Abstract: Background and Objective: Unceasing rise in cases of enteric fever, in particular extensively drug resistant (XDR) strain of Salmonella enterica, has led to a growing threat, leaving only carbapenems and azithromycin as the precious option. In this regard, we determined the burden and clinical course of XDR salmonella in comparison to multidrug-resistant (MDR) and drug sensitive (DS) strains. Methods: A retrospective chart review of 1515 Salmonella Typhi (S.typhi) culture positive patients was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…22 High grade fever is the most common clinical manifestation of enteric fever especially in pediatric age groups which aggravates parental anxiety. 23 In our study 58.7% patients had fever for seven to 14 days before the admission. Majority of them had temperature of more than 100 o F. This observation is comparable with the retrospective review done by Parry et al where the median duration of fever at admission of enteric fever cases was7 days (IQR, 5-14 days).…”
Section: Discussionmentioning
confidence: 42%
“…22 High grade fever is the most common clinical manifestation of enteric fever especially in pediatric age groups which aggravates parental anxiety. 23 In our study 58.7% patients had fever for seven to 14 days before the admission. Majority of them had temperature of more than 100 o F. This observation is comparable with the retrospective review done by Parry et al where the median duration of fever at admission of enteric fever cases was7 days (IQR, 5-14 days).…”
Section: Discussionmentioning
confidence: 42%
“…17 During another study conducted by Fivizia and colleagues in Karachi in 2017-2018, it was observed that the predominant age range in children was 5-6 years. 18 In a study by Gul et al in Lahore, most children were between 4-8 years of age i.e 44.8%. 22 On contrary, a study done at Indus hospital Karachi by Saba Shahid and colleagues showed that children below 5 years of age suffered the most with XDR S.Typhi fever which coincides with our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Expanding dependence is presently being put on the move on thirdperiod cephalosporins and azithromycin. Adding antimicrobial opposition to S. Typhi is a serious general well-being concern, particularly in industrializing nations (Su et al, 2004;Harish and Menezes, 2011;Karkey et al, 2018;Herekar et al, 2022).…”
Section: Antimicrobial Assay Of Homoeopathic Medicine and Controls By...mentioning
confidence: 99%